Pengaruh Latihan Wash game Terhadap Hasil Passing Bawah Siswa Ekstrakurikuler Bola Voli - Hidayat, Nasrul; Hermawan, Irwan; Kosasih, Alam Hadi; Permadi, Asep Angga (Universitas Hamzanwadi, 2025)
This study aims to examine the effect of wash game training on improving lower passing skills in extracurricular volleyball at SMKN 2 Pasundan Garut. This study used an experimental method with a pre-experimental design. The research sample was 14 male volleyball extracurricular students selected through the total sampling technique. The data collection instrument used was the NCSU volleyball test. To measure students' lower passing skills, the initial test and final test were used before and after the wash game training program. Based on descriptive analysis, there was a significant increase in lower passing skills after training. The average pretest score before training was 25.79, while the average posttest score after training increased to 41.00 with an increase of 15.21 points. The t-test resulted in a significance value (2-tailed) of 0.000 which is smaller than 0.05 which means that the difference between the pretest and posttest is significant. The wash game training program proved to be effective in improving students' lower passing skills. In conclusion, the findings suggest that wash game-based training can be an effective alternative to improve volleyball skills, particularly in lower passing, by enhancing teamwork, communication, and player confidence.